Overview of commonly used materials for coal spontaneous combustion prevention. (1st September 2020) - Li, Qing-Wei; Xiao, Yang; Zhong, Kai-Qi; Shu, Chi-Min; Lü, Hui-Fei; Deng, Jun; Wu, Shiliang
Abstract: Coal spontaneous combustion (CSC) is a major concern in the exploitation and utilisation processes of coal. Various technologies for inhibiting CSC have been developed, promoting industrial safety. With consideration of the complexity of the processes involved, efficient fire prevention and control techniques should be developed. Commonly used retardants for CSC prevention were reviewed. Based upon the necessary conditions required for CSC and coal − oxygen reaction mechanism, various materials used in CSC inhibition are analysed in detail and classified into physical-based, chemical-based, as well as composite retardants. The novel composite retardants combine both physical and chemical-based mechanisms in controlling CSC. The advantages and disadvantages of each CSC retardant are discussed and inter-compared. This review can promote research in the most needed areas to develop more efficient and affordable materials for CSC prevention.